2004
DOI: 10.1021/cm035354e
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin-Cored 2,2-Bis(methylol)propionic Acid Dendrimers

Abstract: The synthesis and characterization of dendron-coated porphyrins up to the fifth generation are described. Both free base and zinc-cored tetraphenylporphyrin (TPPH 2 and TPPZn) were used, from which the dendrons were divergently grown using the anhydride of acetonideprotected bis-MPA (acetonide-2,2-bis(methoxy)propanoic anhydride). It is shown that a spacer must be attached to the porphyrin to increase the hydrolytic stability and allow synthesis of higher generations. Direct coupling of dendrons to the porphyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 55 publications
6
65
0
Order By: Relevance
“…[26,30,31] All of these chromophores exhibit strong nonlinear response through excited state absorption of excite triplet states formed by efficient intersystem crossing (ISC) due to spin-orbit coupling induced by the central platinum atom. [14,23,44] R. Westlund et al / Solid-State Optical Power Limiting of Pt-acetylides In our previous publications [26,30,45,46] we also showed how dendritic substituents, based on the 2,2-bis(methylol)propionic acid (bis-MPA) branching unit, attached to the NLO chromophores will not only improve the OPL performance due to site isolation [30] of the chromophore, but also improve the solubility of the chromophores in various solvents. Since many NLO chromophores are both highly conjugated and hydrophobic they tend to p-stack together.…”
Section: Resultsmentioning
confidence: 76%
“…[26,30,31] All of these chromophores exhibit strong nonlinear response through excited state absorption of excite triplet states formed by efficient intersystem crossing (ISC) due to spin-orbit coupling induced by the central platinum atom. [14,23,44] R. Westlund et al / Solid-State Optical Power Limiting of Pt-acetylides In our previous publications [26,30,45,46] we also showed how dendritic substituents, based on the 2,2-bis(methylol)propionic acid (bis-MPA) branching unit, attached to the NLO chromophores will not only improve the OPL performance due to site isolation [30] of the chromophore, but also improve the solubility of the chromophores in various solvents. Since many NLO chromophores are both highly conjugated and hydrophobic they tend to p-stack together.…”
Section: Resultsmentioning
confidence: 76%
“…[24][25][26] However, in order to control parasitic quenching mechanisms as well as introducing more sophisticated photo-activity, some kind of organic cage or complex is needed, as shown e.g., for dendrimers, [27][28][29] two-photon absorbing sensitized lanthanide complexes 30 and porphyrin photo-chemistry. 31,32 It was recently shown that highperformance multi-functional hybrid organic-inorganic hybrid materials can be obtained by a sol-gel procedure; here an organometallic platinum complex with strong triplet excited state absorption was introduced into a laser hardened bulk matrix with high temperature performance. 33 Aqueous based sol-gel methods have the additional advantage that the environmental and health risks are considerably lower compared to methods based on organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of PEG chains to "bow-tie" dendrimers [154]. Two years later, Malmström, Hult and coworkers reported the synthesis and characterization of dendron-coated porphyrins up to the fifth generation [155]. Here, both free base and zinc-cored tetraphenylporphyrin (TPPH 2 and TPPZn) were used, from which the dendrons were divergently grown using 38.…”
Section: 15mentioning
confidence: 99%
“…Scheme 28. Divergent construction of a fourth generation (acetonide-protected) free base porphyrin-cored polyester dendrimer [155].…”
Section: 15mentioning
confidence: 99%